Ni la guerre, ni la paix: campagnes de "stabilisation" et violence structurelle chez les Tlapanèques de la Montaña du Guerrero (Mexique) - Hébert, Martin (Anthropologica, 2022)
Drawing on the growing use of the concept of structural violence in anthropology, the present article examines the impacts of various government interventions and policies that have shaped the Montana region of Guerrero since the 1970s. The consequences of the military campaign waged against the guerrilla movement of Genaro Vazquez Rojas (1969-72), as well as those of State interventions in the region that have been shaped by the policy of "shared development" (1970-76), are considered here through an analysis of their impacts on indigenous communities in the region in general, and on one Tlapanec community—Barranca Tigre—in particular. This analysis sheds considerable doubt on the oft repeated idea that strengthening State structures in marginalized rural areas, as well as promoting greater integration of these areas in the market economy, will promote peace in such regions. Given the nature of the pacification policies described in this article, which are by no means unique to the time and place considered here, we conclude that the Tlapanecs of Guerrero have known, since the 1970s, a sustained level of violence—both direct and structural?that has not been significantly reduced, and has sometimes been amplified, by governmental "stability promoting" interventions in their region.